2022
DOI: 10.1590/1806-9061-2021-1555
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-transport Feed Withdrawal on Welfare and Meat Characteristics of European Quails

Abstract: The objective of this study was evaluate whether pretransport feed withdrawal affects welfare, carcass, and meat characteristics of European quails. A total of 120 European quails were used, with an initial age of 15 days. Bird feed was removed before transport to the slaughterhouse at the following times, which characterised the different treatments: zero hours, three hours, six hours, nine hours and twelve hours. The transport took 54 minutes to cover 27 kilometres to a commercial slaughterhouse. The birds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, Uddin et al (2020) showed that quail diets supplemented with organic acid did not influence carcass traits but increased carcass percentage and liver weight. On the other hand, Silva et al (2022) showed that FR significantly reduced carcass trait percentages of quails, but carcass weight was not affected. In addition, Rønning et al (2009) reported that feed restriction decreased effective body mass, liver, and kidney weight of quails.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, Uddin et al (2020) showed that quail diets supplemented with organic acid did not influence carcass traits but increased carcass percentage and liver weight. On the other hand, Silva et al (2022) showed that FR significantly reduced carcass trait percentages of quails, but carcass weight was not affected. In addition, Rønning et al (2009) reported that feed restriction decreased effective body mass, liver, and kidney weight of quails.…”
Section: Discussionmentioning
confidence: 90%
“…Our results agree partially with Arslan et al (2022), who demonstrated that a laying hen diet supplemented with essential oil (50, 100, and 200 mg/ kg diet) had increased value of serum blood AST due to higher FI and enhanced EP and did not affect serum blood ALT. Silva et al (2022) showed that serum blood corticosterone, total protein, and albumin values were not affected by feed rationing for quails, but glucose value was reduced. Sözcü et al (2021) reported that laying hens reared under feed restriction (120 g/day at 50-51 weeks of age) had a significant decrease in cholesterol, AST, ALT val-ues but no effect on T3, T4, IgG, IgA, IgM.…”
Section: Discussionmentioning
confidence: 96%